2018
DOI: 10.1039/c8sc02471e
|View full text |Cite
|
Sign up to set email alerts
|

High electrical conductivity and high porosity in a Guest@MOF material: evidence of TCNQ ordering within Cu3BTC2 micropores

Abstract: The host–guest system TCNQ@Cu3BTC2 is a striking example of how semiconductivity can be introduced by guest incorporation in an otherwise insulating parent material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(145 citation statements)
references
References 28 publications
10
135
0
Order By: Relevance
“…3 shows the micrographs of the crystals of pristine HKUST-1 and the TCNQ@HKUST-1 host-guest composite material. In line with previous experiments, a Cu-TCNQ coordination polymer 26 can be seen at the surface of the TCNQ@HKUST-1 host-guest composite material. The bands corresponding to both materials were present after deconvolution of the average Raman spectra of each cluster (see Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…3 shows the micrographs of the crystals of pristine HKUST-1 and the TCNQ@HKUST-1 host-guest composite material. In line with previous experiments, a Cu-TCNQ coordination polymer 26 can be seen at the surface of the TCNQ@HKUST-1 host-guest composite material. The bands corresponding to both materials were present after deconvolution of the average Raman spectra of each cluster (see Fig.…”
Section: Resultssupporting
confidence: 91%
“…It is worth mentioning that the conductivity measurements were carried out using mm-sized Cu 3 BTC 2 powders (10-20 mm octahedra) infiltrated with TCNQ, as previously described in the literature. 26 However, we believe that the redispersion phenomenon may also be present in the case of those powdered samples. Previous studies have suggested that TCNQ, aligned within the pores of HKUST-1, leads to a percolation system through which electrons can hop from one pore to the next one.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations